Modelling Aggregate Energy Consumption for Growth in Nigeria - Adekunle, Ahmed Oluwatobi; Abdulmumin, Biliqees Ayoola; Akande, Joseph Olorunfemi; Ajose, Kehinde Gabriel (International Journal of Energy Economics and Policy, 2022)
The principal aims of this study is to modelled the connection of Aggregate energy consumption for growth in Nigeria. Annual time series data is used, ranging from 1985-2020. The study employed ARDL, Toda and Yamamoto approach in examining connection between the variables. The ARDL results with additional stability test shows that short and long run connection exists among the examined variables. The Toda and Yamamoto test reveals unidirectional causalities running among the variables. Furthermore, change in GDP stimulate further consumption of energy in Nigeria.